First reported case of lead-related infective endocarditis secondary to Capnocytophaga canimorsus: 'Dog Scratch' endocarditis. Issue 2 (9th February 2020) - Squire, Gareth; Hetherington, Simon
Abstract : A 76-year-old woman presented with a 6-week history of malaise, night sweats and recurrent fever. She had a background of dilated cardiomyopathy for which she had a cardiac resynchronisation device in situ. She had several hospital admissions across this time with differing diagnoses offered. She received multiple courses of antibiotics with short-term symptom resolution. Blood cultures grew Gram-negative rods and samples were sent to a specialist centre for subtype analysis. A transthoracic echocardiogram revealed thickening of the distal right ventricular lead. A transoesophageal echocardiogram demonstrated a clearer vegetation on this lead. It transpired that she had been scratched by her dog a fortnight before symptom onset. The causal bacterium was reported as Capnocytophaga canimorsus, a bacterium that exists almost exclusively in the saliva and claws of dogs and cats. She received an extended course of antibiotics with eventual removal of the infected device.